Real-Space Vortex Glass Imaging and the Vortex Phase Diagram of SnMo6S8 - Petrović, A.P.; Fasano, Y.; Lortz, R.; Senatore, C.; Demuer, A.; Antunes, A.B.; Paré, A.; Salloum, D.; Gougeon, P.; Potel, M.; Fischer, Ø.; Fasano, Yanina (American Physical Society, 2009)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Université de Genève; Suiza